Multi-Attention and the Horcrux Logic: Justifications for Talking on the Cell Phone While Driving. - Wellner, Galit (Techné: Research in Philosophy & Technology)
Attention has been addressed either as a distinction of a figure from background or as a searchlight scanning of a surface. In both ways, attention is limited to a single object. The aim of this article is to suggest a platform for an interpretation of multi-attention, that is, attention based on a multiplicity of objects and spaces. The article describes how attention can be given to more than one object, based on the experiences of pilots, parents and car drivers.